2008
DOI: 10.1063/1.2965807
|View full text |Cite
|
Sign up to set email alerts
|

Current percolation in ultrathin channel nanocrystalline silicon transistors

Abstract: The ultrathin channel nanocrystalline silicon transistor shows greatly improved switching performance and has demonstrated its candidacy for low power applications. In this work, by careful observation of the current-voltage and threshold voltage characteristics, we find that current percolation occurs when the channel is thinner than 3.0 nm due to strong quantum confinement induced large potential variations over the channel. We show that the device channel width must be at least 0.3 m to avoid percolative "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…In nanocrystalline ZnO, the electron trapping sites at grain boundaries control electron conduction [20][21][22][23][24] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In nanocrystalline ZnO, the electron trapping sites at grain boundaries control electron conduction [20][21][22][23][24] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Em uma ordem de magnitude menor, efeitos quânticos começam a se manifestar possibilitando aos elétrons pular de um condutor para outro, perdendo-se assim as características básicas do dispositivo. 27 O trabalho que deu início as pesquisas sobre os problemas relacionados aos processos de miniaturização, em particular por problemas dentro da teoria da computação e dos sistemas computacionais, foi o estudo entre consumo de energia e computação, feito por R. Landauer, no ano de 1961. 28 Em 1973, C. Bennett mostrou matematicamente a possibilidade de realizar operações computacionais reversíveis, resultando na possibilidade de desenvolvê-las sem dissipação de energia.…”
Section: Breve Históricounclassified
“…Because of shrinking of device size down to 10 nm, the statistical variations due to the traps and dopants becomes more severe. Moreover, it is also problematic that there are an abnormally large threshold voltage (VT) shift that may belong to the 6-sigma tail of the statistical distribution [2]- [5]. It has been reported that chained traps and dopants forming a cluster of potential peaks on the channel surface results in the tail distribution.…”
Section: Introductionmentioning
confidence: 99%